2018
DOI: 10.1139/cjpp-2017-0651
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective influence of quercetin and ellagic acid on thioacetamide-induced hepatotoxicity in rats

Abstract: Despite all the studies performed to date, therapy choices for liver injuries are very few. Therefore, the search for a new treatment that could safely and effectively block or reverse liver injuries remains a challenge. Quercetin (QR) and ellagic acid (EA) had potent antioxidant and anti-inflammatory activities. The current study aimed at evaluating the potential hepatoprotective influence of QR and EA against thioacetamide (TAA)-induced liver toxicity in rats and the underlying mechanism using silymarin as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…All dosages of quercetin decreased AST levels in the serum of arthritic rats, demonstrating the hepatoprotective potential effect of this flavonoid. This effect has been verified in other studies, and it is suggested to be due to the antioxidant capacity of quercetin through the elimination of reactive oxygen species, inhibition of lipoxygenase and cyclooxygenase, and stabilization of cell membranes …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…All dosages of quercetin decreased AST levels in the serum of arthritic rats, demonstrating the hepatoprotective potential effect of this flavonoid. This effect has been verified in other studies, and it is suggested to be due to the antioxidant capacity of quercetin through the elimination of reactive oxygen species, inhibition of lipoxygenase and cyclooxygenase, and stabilization of cell membranes …”
Section: Discussionsupporting
confidence: 68%
“…All dosages of quercetin decreased AST levels in the serum of arthritic rats, demonstrating the hepatoprotective potential effect of this flavonoid. This effect has been verified in other studies, [50][51][52] and it is suggested to be due to the antioxidant capacity of quercetin through the elimination of reactive oxygen species, 53,54 inhibition of lipoxygenase and cyclooxygenase, and stabilization of cell membranes. 53,55,56 In the present study, we observed increased ROS and TBARS levels in the untreated arthritic group, which may be owing to the production of ROS as a result of inflammation, leading to the destruction of cartilage and bone, neutrophil degranulation, and the release of various potentially harmful enzymes.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, EA decreased the MDA level while increased the GPx activity in the liver tissue. They suggested that EA improves hepato-toxicity through the antioxidant effects (Afifi, Ibrahim, & Galal, 2018).…”
Section: Antioxidant Effects Of Pomegranate and Ellagic Acidmentioning
confidence: 99%
“…Changes in the concentration of the product were assessed by measuring the fluorescence level during the elongation phase of PCR. The real-time PCR conditions were performed as follows: 95 °C for 5 min (initial denaturation) and then 40 cycles at 95 °C for 15 s, 60 °C for 20 s, and 72 °C for 15 s. After the final cycle, the melting curve analysis of all samples was performed through one cycle of 95 °C for 15 s, 58 °C for 15 s, and 95 °C for 15 s. B-actin is used as internal control (Afifi et al, 2018). Negative controls that were free of the template were included in each experiment.…”
Section: Quantitative Real-time Pcr Analysis Of Gpx and Sod Genesmentioning
confidence: 99%